Single crystals of LnFeAsO1-xFx (Ln=La, Pr, Nd, Sm, Gd) and Ba1-xRbxFe2As2: growth, structure and superconducting properties - Karpinski, J.; Zhigadlo, N.D.; Katrych, S.; Bukowski, Z.; Moll, P.; Weyeneth, S.; Keller, H.; Puzniak, R.; Tortello, M.; Daghero, D.; Gonelli, R.; Maggio-Aprile, I.; et al. (Elsevier, 2009)
Fil: Fasano, Y. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; University of Geneva; Suiza